The Hypothesis of Change from Above in the History of English: State of the Art and Perspectives - Lavidas, Nikolaos (Studia Anglica Posnaniensia, 2019)
The present paper presents the state of the art of research related to hypothesized changes from above in the diachrony of English. A main aim of the paper is to show how the cooperation of various perspectives can open new directions in the research of language change. We examine the main aspects of a definition of the change from above. We investigate the various perspectives through which the concept of change from above, as an “importation of elements from other systems” (Labov 2007), has been considered a significant factor for the development of English. We show that any attempt to investigate the presence or role of change from above includes the parameters of prestige, distribution of old and new forms, diffusion, gender, and linguistic ideology. Finally, we discuss typical examples of development of patterns and characteristics of English that have been analyzed as influenced by change from above, as well as the prestige dialects / languages and contexts that have been regarded as facilitating a hypothesized change from above (Latin, Anglo-Norman, standardization, prescriptivism, networks and individuals). We argue that the articles of the present special issue provide stable criteria that are required in any attempt to test the hypothesis of change from above in the development of English.